THE EUROPEAN UNION AND ITS CONTRIBUTION TO THE DEVELOPMENT OF THE INTERNATIONAL CRIMINAL COURT - Strapatsas, Nicolaos (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2002)
The following essay compares and contrasts the positions of the Council and Parliament of the European Union regarding the International Criminal Court. The European Council represents the governments of the EU Member States whereas the European Parliament represents the European peoples. Although the European Council is not bound by the European Parliament’s resolutions, the presidency must consult the Parliament on the main aspects and the basic choices of common foreign and security policy. Overall, the Parliament’s positions appear more liberal than those of the Council. The essay highlights the controversial issues raised at the Rome Diplomatic Conference involving EU Member States. On certain key issues, France and the United Kingdom adopted attitudes clearly protective of their individual interests as permanent members of the United Nations Security Council and thus negatively affected the outcome in Rome. The essay also illustrates the European Union’s indirect role in the development of the International Criminal Court through the support and funding of Non-governmental Organisations for that specific purpose. It describes developments since the Rome Conference, and outlines some future considerations regarding the relationship between the European union and the ICC.